2018
DOI: 10.1371/journal.pone.0207185
|View full text |Cite
|
Sign up to set email alerts
|

Demographic risk factors for mid-urethral sling failure. Do they really matter?

Abstract: Age, obesity and vaginal deliveries (VD) are recognized risk factors for stress urinary incontinence (SUI). According to many authors, the abovementioned risk factors for incontinence also increase the risk of mid-urethral sling (MUS) failure. Our aim was to evaluate the objective and subjective effectiveness of retropubic MUS in 12 months observation, relative to the three potential risk factors of failure: obesity, age and VDs. A prospective observational study including 238 women who underwent retropubic MU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…However, to date it is unknown whether these obstetrical factors such as delivery mode, obstetric anal sphincter injury, levator ani avulsion, and fetal factors also impact surgical outcomes in women with SUI. Parity is, to our knowledge, the only obstetrical factor previously studied [13,15]. Laterza et al evaluated the effect of parity at the time of surgery on short-and long-term outcomes in women who underwent SUI surgery by MUS [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to date it is unknown whether these obstetrical factors such as delivery mode, obstetric anal sphincter injury, levator ani avulsion, and fetal factors also impact surgical outcomes in women with SUI. Parity is, to our knowledge, the only obstetrical factor previously studied [13,15]. Laterza et al evaluated the effect of parity at the time of surgery on short-and long-term outcomes in women who underwent SUI surgery by MUS [15].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high cure rates, there is still a group of women for whom the surgery fails in obtaining continence. Some of the risk factors identified are age at time of surgery, obesity, concomitant pelvic organ prolapse surgery, and surgical technique [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies covering the topic of obesity and SUI are retrospective and the findings are heterogeneous. A prospective observational study including 238 women who underwent retropubic MUS implantation with 12‐month follow‐up failed to find any difference in objective and subjective outcomes 10 . McKenna et al 24 followed a cohort of women for 5 years who underwent retropubic sling procedures and found significantly worse subjective and objective results in obese patients (98% vs 71%, P = .004).…”
Section: Discussionmentioning
confidence: 99%
“…A prospective observational study including 238 women who underwent retropubic MUS implantation with 12-month follow-up failed to find any difference in objective and subjective outcomes. 10 McKenna et al 24 followed a cohort of women for 5 years who underwent retropubic sling procedures and found significantly worse subjective and objective results in obese patients (98% vs 71%, P = .004). Berger et al 25 in a retrospective cohort of retropubic TVT subjects, found that obese women had…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment is the preferred option for women with stress urinary incontinence in whom conservative management strategies have failed [11]. According to the available literature, mid-urethral slings are both more effective and safer than other surgical treatment modalities [12], with objective and subjective cure rates of retropubic TVT ranging from 71% to 97% [13,14]. There has also been an ongoing discussion considering other treatment options such as fascial slings.…”
Section: Discussionmentioning
confidence: 99%